A Way to Address Inherent Weakness in Conceiving the Ground Plane Geometry for a Microstrip Antenna - Chandreyee Sarkar; Sk Rafidul; Chandrakanta Kumar; Debatosh Guha (IEEE Open Journal of Antennas and Propagation, 2024)
This work presents an insight into the nature of ground plane (GP) current of a microstrip patch which is truly adverse in terms of generating cross-polar (XP) fields and minimally contributing to the primary radiation. This study also uses a theoretical basis in exploring a simple solution to mitigate the high XP values, specifically over the diagonal planes (D-planes). This actually turns out to be an engineered GP by clipping off its four corners. This has been thoroughly studied for a set of representative patch geometries and experimentally verified. A consistent XP reduction by 12–13 dB over D-planes has been ensured without affecting the impedance matching or antenna gains. This eventually results in cross-polar discrimination (XPD) of the order of 25–31 dB uniformly over the full range of operating bandwidth. In addition, the design is advantageous in terms of reduction in antenna size or the deployment area. Such a simple low-cost design appears as truly improved alternative to a typical standalone microstrip radiator for practical applications.